Targeted Delivery of Liposomal Temozolomide Enhanced Anti-Glioblastoma Efficacy through Ultrasound-Mediated Blood-Brain Barrier Opening - Zhuqing Song; Xiuxian Huang; Jieqiong Wang; Feiyan Cai; Ping Zhao; Fei Yan (MDPI AG, 2021)
Glioblastoma (GBM) is the commonest form of primary brain tumor in the central nervous system, with median survival below 15 months and only a 25% two-year survival rate for patients. One of the major clinical challenges in treating GBM is the presence of the blood-brain barrier (BBB), which greatly limits the availability of therapeutic drugs to the tumor. Ultrasound-mediated BBB opening provides a promising approach to help deliver drugs to brain tumors. The use of temozolomide (TMZ) in the clinical treatment of GBM has been shown to be able to increase survival in patients with GBM, but this improvement is still trivial. In this study, we developed a liposomal temozolomide formulation (TMZ-lipo) and locally delivered these nanoparticles into GBM through ultrasound-mediated BBB opening technology, significantly suppressing tumor growth and prolonging tumor-bearing animal survival. No significant side effects were observed in comparison with control rats. Our study provides a novel strategy to improve the efficacy of TMZ against GBM.